Gestational Age and Risk of Mortality in Term-Born Critically Ill Neonates Admitted to PICUs in Australia and New Zealand*. Issue 8 (August 2020) - Namachivayam, Siva P.; Carlin, John B.; Millar, Johnny; Alexander, Janet; Edmunds, Sarah; Ganeshalingham, Anusha; Lew, Jamie; Erickson, Simon; Butt, Warwick; Schlapbach, Luregn J.; Ganu, Subodh; Festa, Marino; et al.
Abstract : Objectives: Gestational age at birth is declining, probably because more deliveries are being induced. Gestational age is an important modifiable risk factor for neonatal mortality and morbidity. We aimed to investigate the association between gestational age and mortality in hospital for term-born neonates (≥ 37 wk') admitted to PICUs in Australia and New Zealand. Design: Observational multicenter cohort study. Setting: PICUs in Australia and New Zealand. Patients: Term-born neonates (≥ 37 wk) admitted to PICUs. Interventions: None Measurements and Main Results: We studied 5, 073 infants born with a gestational age greater than or equal to 37 weeks and were less than 28 days old when admitted to a PICU in Australia or New Zealand between 2007 and 2016. The association between gestational age and mortality was estimated using a multivariable logistic regression model, adjusting for age, sex, indigenous status, Pediatric Index of Mortality version 2, and site. The median gestational age was 39.1 weeks (interquartile range, 38.2–40 wk) and mortality in hospital was 6.6%. Risk of mortality declined log-linearly with gestational age. The adjusted analysis showed a 20% (95% CI, 11–28%) relative reduction in mortality for each extra week of gestation beyond 37 weeks. The effect of gestation was stronger among those who received extracorporeal life support: each extra week of gestation was associated with a 44% (95% CI, 25–57%) relative reduction in mortality. Longer gestation was also associated with reduced length of stay in hospital: each week increase in gestation, the average length of stay decreased by 4% (95% CI, 2–6%). Conclusions: Among neonates born at "term" who are admitted to a PICU, increasing gestational age at birth is associated with a substantial reduction in the risk of dying in hospital. The maturational influence on outcome was more strongly noted in the sickest neonates, such as those requiring extracorporeal life support. This information is important in view of the increasing proportion of planned births in both high- and low-/middle-income countries. Abstract : Supplemental Digital Content is available in the text.